The Salafiyah-Khalafiyah Integrative Curriculum Model at the Darul Ma'arif NU Rejang Lebong Islamic Boarding School - Faham Syah; Muhammad Istan; Eka Apriyani (UIN Fatmawati Sukarno Bengkulu, 2026)
Background: Islamic boarding schools (pesantren) face the challenge of maintaining their traditional identity while responding to the demands of modernity, particularly regarding the relevance of the curriculum to scientific developments and societal needs. The Darul Ma'arif NU Islamic Boarding School in Rejang Lebong developed an integrative Salafiyah-Khalafiyah curriculum that combines the tradition of studying yellow books with the formal and vocational education systems.Methods: This research used a qualitative approach with a longitudinal case study design for the period 2021–2025. Data were collected through analysis of curriculum documents, in-depth interviews with Islamic boarding school administrators, and observations of learning activities. Data analysis was conducted through the stages of thematic reduction, presentation, and drawing conclusions using the interactive model of Miles, Huberman, and Saldaña.Results: The Islamic boarding school curriculum was developed through a multi-level adaptive integration of the Salafiyah tradition, which focuses on deepening classical Islamic knowledge, with the Khalafiyah approach, which emphasizes 21st-century competencies, and the Merdeka Curriculum. The curriculum is organized holistically within the 24-hour Islamic boarding school ecosystem, encompassing formal education, Islamic boarding schools (madrasah diniyah), and Islamic boarding school activities.Conclusion: This integrative curriculum model successfully maintains the Islamic boarding school's identity while increasing the relevance of education to local social and economic needs. This research offers the concept of multilevel adaptive integration as a theoretical contribution to the development of contemporary Islamic boarding school curricula.